2023
DOI: 10.21203/rs.3.rs-2644364/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of a selective YTHDC1 inhibitor that targets acute myeloid leukemia

Abstract: N6-methyladenosine (m6A) is the most prevalent modification of eukaryotic RNA, which is recognized by m6A-binding proteins (“readers”) and thereby mediates multiple biological processes. Dysregulation of the m6A readers has been linked to various pathologies, but the therapeutic potential of small molecule inhibitors targeting the m6A readers is unknown. Here we report the identification and characterization of a highly potent and selective first-in-class inhibitor (YL-5092) of YT521-B homology (YTH) domain-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…On the other hand, a bigger and more lipophilic bromide substituent present in compound 24 resulted in a 2-fold decrease in potency (IC 50 = 2 μM) in comparison to compound 25. Because of the positive effect observed with carboxylic acid functionality, we also prepared derivatives of carboxylic acid (28,29) and benzyl alcohol derivative 30 in the para position. However, these compounds did not exhibit improved binding compared to the ones with functional groups in meta position, presumably due to an unfavorable orientation of the substituents that lead toward solvent exposed area out of the pocket.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, a bigger and more lipophilic bromide substituent present in compound 24 resulted in a 2-fold decrease in potency (IC 50 = 2 μM) in comparison to compound 25. Because of the positive effect observed with carboxylic acid functionality, we also prepared derivatives of carboxylic acid (28,29) and benzyl alcohol derivative 30 in the para position. However, these compounds did not exhibit improved binding compared to the ones with functional groups in meta position, presumably due to an unfavorable orientation of the substituents that lead toward solvent exposed area out of the pocket.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The crude product was purified using flash column chromatography (SiO 2 ; EtOAc/Hept = 2:1) and the desired compound was obtained as a white solid (0.034 g, 69%). 1 (28). The N 9 alkylation was performed following General procedure 1 using 2,6-dichloropurine 44 (0.2 g, 1.06 mmol) and methyl-4-(bromomethyl)benzoate (0.242 g, 1.06 mmol).…”
Section: -(3-(2h-tetrazol-5-yl)benzyl)-2-chloro-n-methyl-9h-purin-6am...mentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Other studies in the literature have reported inhibition using rather promiscuous binders providing limited selectivity towards proteins of the YTH family, [23][24][25] except for a recent report which describes a selective YTHDC1 inhibitor identified by in vitro high-throughput screening followed by a structure-based optimization. 26 In this study, we present a structure-based design campaign aimed at developing a potent and selective ligand of YTHDC1. Additionally, we provide a biochemical evaluation (HTRF assay, ITC, TSA, X-Ray) and report a direct connection between YTHDC1 inhibition and the effect on the cell proliferation of acute monocytic leukemia (THP-1, MOLM-13, NOMO1).…”
Section: Introductionmentioning
confidence: 99%